A cross-sectional survey unveiling the imperatives for continuing education and discipline development in pain medicine - Ren Jiang; Ren Jiang; Hong Li; Zhiyou Peng; Yanfeng Zhang; Xianhui Kang; Zhiying Feng (Frontiers in Medicine)
ObjectiveThis study aims to investigate persistent gaps in pain medicine education and unmet training needs, while exploring the significance of continuing education in driving disciplinary evolution.MethodsA questionnaire was distributed online in the form of an e-Questionnaire link to the directors of the Pain Medicine Departments of 417 hospitals (covered all hospitals) in Zhejiang Province in China. This questionnaire aimed to identify the problems and needs in continuing education for pain medicine. Subsequently, a questionnaire link was sent to 163 physicians nationwide who had undergone advanced training in the Pain Medicine Department to survey the existing problems and needs in advanced training.ResultsThe survey revealed uneven development of pain medicine, with secondary hospitals notably lagging in pain clinic establishment (51.3% vs. 69.9% in tertiary hospitals). The number of pain physicians is insufficient, and their overall academic qualifications need to be improved. Most directors (81.9%) have a strong willingness to enhance their professional capabilities, recommending advanced training. The number of advanced trainee has increased significantly, most physicians said that inpatient teaching accounts for about 3/4 of the advanced training duration. Case-based learning is the most popular between instructors (93.3%) and advanced trainees (82.2%). 46% of physicians reported having no opportunities for independent or semi-independent outpatient consultation, highlighting insufficient clinical practice opportunities. Additionally, Most physicians (93.3%) are satisfied with their instructors.ConclusionThe findings from this cross-sectional survey underscore the pressing need for a more robust and standardized continuing education framework in pain medicine in China.